PENGARUH KOMISARIS INDEPENDEN, KOMITE MANAJEMEN RISIKO DAN CHIEF RISK OFFICER TERHADAP PENERAPAN ENTERPRISE RISK MANAGEMENT (Studi pada Lembaga Jasa Keuangan Non Bank yang terdaftar di Bursa Efek Indonesia tahun 2014-2016) - Hartantri Wahyu Andari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The purpose of this research is determine the effect of independent commissioners, risk management committees, and chief risk officers on the implementation of enterprise risk management at the Non Bank Financial Services Institution (LJKNB) listed on the Indonesia Stock Exchange 2014-2016 and analyze the effects simultaneously and partially. The sample in this research is 23 LJKNB in ​​Indonesia by using sampling technique that is purposive sampling. This study uses secondary data with the method used is logistic regression analysis method. Based on the results of data processing, it is found that simultaneously independent commissioner variables, risk management committee, and chief risk officer significantly influence the implementation of enterprise risk management in Non Bank Financial Services Institution listed in Indonesia Stock Exchange period 2014-2016. The influence of independent commissioner variable partially has no effect on the application of enterprise risk management in Non Bank Financial Services Institution listed in Indonesia Stock Exchange period 2014-2016. Meanwhile, the risk management committee and chief risk officer have a positive and significant impact on the implementation of enterprise risk management in Non Bank Financial Services Institution listed in Indonesia Stock Exchange period 2014-2016. Keywords: Independent Commissioners, Risk Management Committee, Chief Risk Officer, Enterprise Risk Management